Pengembangan Kawasan Wisata Tamamelong Berbasis Pemberdayaan Masyarakat di Desa Patikarya Kepulauan Selayar - Erfin Kurniawan; Afra Donatha Nimia Makalew; Nizar Nasrullah (http://arl.faperta.ipb.ac.id/, 2022)
This research was conducted in several tourist areas in Patikarya Village, Bontosikuyu District. Each part of the area was identified. This research examines community participation in regional planning and landscape planning of tourist areas. The results of this study are in accordance with the tourism suitability ana;lysis, where the overlay results of all biophysical conditions presented in the Patikarya Village area are divided into three classes of land suitability for tourism, there is no unsuitable land (S4) so that in general Patikarya Village is suitable for tourism development. The tourism suitability class with the tourism suitability index is very suitable (S1) with an area of 674.82 ha or 39.12% and the appropriate class (S2) is 892.34 ha or 51.73%. For the unsuitable tourism suitability index (S3), the area of 157.84 ha or 9.15% is in a dry forest area so it should be maintained as a conservation area with a minimum development of tourism supporting facilities. In the analysis of community acceptability, based on the answers from the acceptability questionnaire to residents and visitors around Tamamelong as many as 30 respondents, they gave a positive response to the existence of Tamamelong if it develops into a sustainable tourist spot. The result of atudy is a plan that consists of a space plan, circulation, vegetation as well as activity and facility plan. In addition, there is also a plan for the carrying capacity of the area so that the sustainability of the area can be maintained.